Political reforms and political parties in Colombia: when change is the rule - Batlle, Margarita (2013)
This article analyzes the different electoral reforms that have taken place since 1990 and the changes that have characterized the party system in Colombia, mainly in terms of fragmentation and volatility of preferences, with an emphasis on the competition that takes place at the national level and on the origin and dynamics of the new coalition government established by President Juan Manuel Santos in 2010. In addition, we observe the configuration created by the regional and local elections of October 2011 and we discuss on the relationship between electoral regulations and the post conflict scenary. In particular, we deal with questions about the future of Colombian representative institutions, especially rules that determine access to elected office and a possible political participation of demobilized guerrillas. In that sense, it is argued that while the objectives of previous reforms were to achieve higher levels of governance, this new context may put the discussion on the need to sacrifice governance for achieving greater representation back in the center of the debate.